The Routledge international handbook of learning - Jarvis, Peter, 1937-; Watts, Mary H. (London, ENK. : Routledge, 2012)
As our understanding of learning focuses on the whole person rather than individual aspects of learning, so the process of learning is beginning to be studied from a wide variety of perspectives and disciplines. This handbook presents a comprehensive overview of the contemporary research into learning.